2016
DOI: 10.1002/mawe.201600487
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of ferrite nanopowders for epoxy‐barium hexaferrite‐nanocarbon composites for microwave applications

Abstract: The effect of the synthesis conditions (type of chemical reagents, temperature of treatment) on phase composition and morphology of ferrite nanopowders containing barium hexaferrite was investigated. X-ray diffraction studies confirm the presence of two phases in synthesized powders -Fe 2 O 3 and BaFe 12 O 19 (BaM) -and ratio between these phases depends on the temperature of powder treatment at last stage of the synthesis. Electron microscopy studies showed that prepared ferrite powders consist of hexagonal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Precursors Fe(NO3)3 and Ba(NO3)2 were taken in 12:1 proportions respectively. Details of synthesis BaFe12O19 powder are presented in 29 . Measurements of magnetic susceptibility in the temperature range 300-850 К as well as XRD analysis 29 have shown that obtained BaFe12O19 powder has the hexaferrite phase only.…”
Section: Methodsmentioning
confidence: 99%
“…Precursors Fe(NO3)3 and Ba(NO3)2 were taken in 12:1 proportions respectively. Details of synthesis BaFe12O19 powder are presented in 29 . Measurements of magnetic susceptibility in the temperature range 300-850 К as well as XRD analysis 29 have shown that obtained BaFe12O19 powder has the hexaferrite phase only.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies were carried out to investigate the effects of ferrite volume fraction in the composite on microwave absorption. The importance of such materials was confirmed by numerous extensive studies developing new effective microwave-absorbing ferrite/polymer composites [28][29][30].…”
Section: Introductionmentioning
confidence: 96%
“…Гексаферриты М-типа имеют высо-кие значения поля магнитной кристаллографической анизотропии и способны работать в этом диапазоне. Данные материалы перспективны для разработки и создания функциональных устройств СВЧ-электроники: вентили, циркуляторы, фазовращатели, элементы антенн приемопередачи, а также эффективных поглотителей ЭМИ для обеспечения электромагнитной совместимос-ти [25][26][27][28][29][30]. Допирование или замещение гексаферрита бария различными диамагнитными ионами приводит к значительному изменению магнитных характеристик и, как следствие, к изменению рабочего диапазона частот.…”
Section: Introductionunclassified